Evaluation of phonological awareness skills in educable children with down's syndrome (mental age of 7 to 12 Years) resident in Isfahan, Iran - Samira Tavakol; Bijan Shafiei; Leila Ali Nia (Vesnu Publications, 2012)
Introduction: Learning phonological awareness skills plays a very important role in the course of speech and language development and throughout academic education in that these skills help children express their mental concepts more precisely. The aim of the present research was to determine levels of phonological awareness competency among educable children with Down's syndrome whose mental age ranged between 7 and 12 years and were resident of Isfahan, Iran. Materials and Methods: In this descriptive-analytic study, all Isfahanian children with Down's syndrome were individually assessed by a phonological awareness test and their scores on different subtests of this test were recorded on a separate sheet exclusively designed for this purpose. Data were statistically analyzed via t-test using SPSS software version 16. Results: Although a superior performance was found in girls, there was no significant difference between boys and girls as far as phonological awareness skills were concerned. In both genders, the highest average score of phonological awareness competency across 12 areas, which were covered by the above-mentioned test, pertained to phonemic synthesis and the lowest average score of such competency was observed in the awareness of middle phoneme. Ranked from simplest to most complex, the following order of competency in phonological skills was observed for both male and female subjects: recognition of the first phoneme, recognition of the last phoneme, awareness of the last phoneme, rhyme detection, alliteration and omission of the first and the middle phoneme. Conclusion: Study results showed that, as a group, phonological awareness skills of girls were superior to those of boys but there were not statistically significant differences between them regarding these skills. This superiority can probably be explained by faster speech and language development in girls and their relatively more advanced use of speech and language skills as it is the case in normal population. Keywords: Down's syndrome, Phonological awareness, Children